Eubacterium limosum modulates gut microbiota and produces anti-inflammatory metabolites to alleviate DSS-induced colitis - Lu, Yao; Tang, Huijing; Fan, Qianhua; Lan, Ruiting; Lin, Xiaoying; Zhang, Shuwei; Liu, Liyun; Xu, Jianguo (Frontiers in Immunology, 2025)
IntroductionInflammatory bowel disease (IBD) is a chronic inflammatory condition of the intestine, for which no cure currently exists. The gut microbiota play a critical role in ameliorating IBD, and Eubacterium limosum has emerged as a potential probiotic with anti-inflammatory properties. However, the specific anti-inflammatory effects of E. limosum and the underlying mechanisms remain largely unexplored.MethodsThe E. limosum strain El1405 was utilized to evaluate its effects on dextran sodium sulfate (DSS)-induced murine colitis. The structural changes in intestinal microbiota were assessed using 16S rRNA gene sequencing. Inflammatory cytokines in the colon and serum were measured via enzyme-linked immunosorbent assay, while metabolomics was employed to analyze metabolites present in both the colon and serum.ResultsThe supplementation with E. limosum El1405 significantly reduced the disease activity index, colon shortening, and colonic histopathological lesions. El1405 reshaped the intestinal microbiota community structure, resulting in a significant increase in the abundance of Bacteroides acidifaciens, Bacteroides thetaiotaomicron, Mucispirillum schaedleri, Phocaeicola vulgatus (formerly Bacteroides vulgatus), and Akkermansia muciniphila, while concurrently decreasing the abundance of Escherichia coli and Enterococcus faecalis. The E. limosum intervention downregulated IL-17 signaling and reduced levels of inflammatory cytokines associated with IL-17 signaling, including IL-6, IL-17, TNF-α, IL-21, IL-22, and GM-CSF. E. limosum could induce anti-inflammatory effects by altering the serum metabolome of mice, especially producing anti-inflammatory metabolites such as indole-3-acetic acid and indole-3-lactic acid.DiscussionThis study demonstrated the beneficial effects of E. limosum El1405 on DSS-induced colitis in mice, by modulating gut microbiota, reducing inflammatory cytokines in the colon and serum, and increasing anti-inflammatory metabolites in the serum. All contribute to the downregulation of IL-17 signaling and the alleviation of colitis. E. limosum supplementation may represent a promising probiotic candidate for IBD prevention.